2017
DOI: 10.1002/pen.24689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atmospheric plasma treatment on adhesion and tribology of aromatic thermoplastic polymers

Abstract: After cold plasma treatment of poly(ethylene terephthalate) and poly(ether‐ether ketone) surfaces by dielectric barrier discharge (DBD) under atmospheric (air) conditions, variations in surface chemistry, and morphology were investigated in relation with adhesion and tribological properties. According to XPS measurements, surface oxidation caused the formation of low molecular weight moieties of carboxylic acids. The latter resulted in more hydrophilic surfaces according to water contact angle measurements, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…An efficient method with high industrial relevance is flame impingement. Treatment with defined plasmas, e.g., low pressure plasma, atmospheric plasma, or corona, in the presence of different gases gives a better control of chemical modification [5][6][7][8][9][10][11][12][13][14][15][16][17]. However, only the PEEK segments on the outermost surface layer are converted to functional groups like carboxyl, hydroxyl, carbonyl, and amide.…”
Section: Introductionmentioning
confidence: 99%
“…An efficient method with high industrial relevance is flame impingement. Treatment with defined plasmas, e.g., low pressure plasma, atmospheric plasma, or corona, in the presence of different gases gives a better control of chemical modification [5][6][7][8][9][10][11][12][13][14][15][16][17]. However, only the PEEK segments on the outermost surface layer are converted to functional groups like carboxyl, hydroxyl, carbonyl, and amide.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, our last work [73] elaborated on the effect of atmospheric DBD plasma on the tribological behaviour of PET under various test conditions (3 "dry" normal load and "run-out lubrication" constant normal load conditions). The effect of DBD plasma treatment on the characterization of the surface was interpreted as an enhancement of the surface energy and reduction in the surface roughness due to the melting of surface asperities.…”
Section: Tribological Behaviour Of the Surface Of Polymers Treated Bymentioning
confidence: 99%
“…Polar oxygen groups are created on the surface by the radicals reacting with oxygen in the air. Al-Maliki et al [11] determined that post-treatment there was an increase in oxygen content and a decrease in carbon content forming polar functional groups that increased the wettability of the surface thus making the surface more hydrophilic. They attributed plasma treatment's ability to increase surface energy to the combination of two main factors, increased wettability and increased surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The change in surface roughness may be different depending on the type of treatment used. In [11] and [13] it was found that using dielectric-barrier discharge (DBD) treatment for one minute causes a flattening of the surface rather than a roughening. Hergelová et al [14] again found that short treatment times caused flattening, but with extended treatment time, the roughness would start to increase rapidly.…”
Section: Introductionmentioning
confidence: 99%